Melanoma of the Breast with Smoothened (SMO) Mutation: Case Report and review of the Literature - L. Clark Jennifer; Lee Connie; Kandil Dina; Hutchinson Lloyd; Khan Ashraf (Journal of Cancer Genetics And Biomarkers, 2019)
We report the case of a 75 year-old female with past history of ampullary adenocarcinoma presenting with a rapidly enlarging breast mass, initially misclassified on fine needle aspiration as a probable sarcoma, which was ultimately diagnosed as melanoma on resection in the absence of a known cutaneous primary lesion. Next-generation sequencing (NGS) of the tumor revealed a mutation in the Smoothened oncogene (SMO) of unknown significance and wild-type BRAF. To our knowledge, SMO mutation in melanoma of any site has not been previously reported, though the effectiveness of SMO inhibitors has been studied in both in vivo and in vitro models of melanoma. Currently, these inhibitors have not been studied in SMO mutant melanoma. The patient declined further therapy after resection due to multiple comorbidities. She expired two years after presenting with the breast mass from complications of high grade urothelial carcinoma.
Keywords: breast